Didactical Design with Problem Posing to Overcome Epistemological Obstacles in Problem Solving - Firmina Eka; Sugiatno Sugiatno; Munaldus Munaldus; Hamdani Hamdani; Silvia Sayu (Universitas Syiah Kuala, 2023)
Problem-solving activities allow students to apply mathematical knowledge and connect other mathematical abilities more deeply. However, based on the situation in the field, students still experience epistemological obstacles in solving problems on Straight Line Equation material, especially issues in story form. This study aims to overcome students' epistemological obstacles in problem-solving using didactic design with a problem-posing approach. This research is qualitative research with a didactical design research method. Six students at one of the schools in West Kalimantan, Indonesia, were the subjects of this research. Tests, interviews, and observation guidelines were used as data collection instruments. The research data obtained were analyzed, reduced, and presented in narrative form. The results showed that epistemological obstacles can be overcome after implementing didactic design with problem posing. This finding has the same pattern as previous research findings, although on different materials and scaffolding. Therefore, didactical design with problem posing can be used as one of the alternative learning designs for straight-line equation material in the classroom.